The Relationship between Pinguecula and Diabetes Mellitus: A Comparative Cross-Sectional Study - Hisham M. Jammal; Mohammed Abu-Ameerh; Jamila G. Hiasat; Sara Issa; Muawyah Al Bdour (Journal of Ophthalmology)
Purpose. To assess the relationship between diabetes mellitus (DM) and the presence of pinguecula and to identify other risk factors associated with pinguecula in patients attending the eye clinic at two tertiary university hospitals in Jordan. Methods. This was a comparative cross-sectional hospital-based study of 241 consecutive patients (122 patients with DM and 119 patients with no diabetes). All patients underwent complete ophthalmic examination, and data were collected regarding age, sex, occupational activity, presence and grade of pinguecula, glycosylated hemoglobin (HbA1c), and presence of diabetic retinopathy. Results. The mean (standard deviation, SD) ages of the DM and non-DM groups were 59.5 (10.8) years and 59.0 (11.6) years (p-value = 0.729), respectively. There was no significant difference in the prevalence of pinguecula between the diabetic and nondiabetic groups (66.4% vs. 66.5%, p=0.998). Multivariate logistic regression analysis revealed that only outdoor occupational activity (OR = 5.16, 95% CI: 1.98–13.44, p=0.001) was associated with increased prevalence of pinguecula. DM was not significantly associated with pinguecula (OR = 0.96, 95% confidence interval (CI): 0.55–1.67, p=0.873). Neither age nor sex were significantly associated with pinguecula (p-value = 0.808, p-value = 0.390), respectively. Conclusion. DM was not significantly associated with the development of pinguecula in this Jordanian population. The prevalence of pinguecula was significantly associated with an outdoor occupational activity.